Manners, norms and transgressions in the history of English literary and linguistic approaches - Jucker, Andreas H.; Taavitsainen, Irma (Pragmatics & beyond ;, 2020)
"This volume traces the multifaceted concept of manners in the history of English from the late medieval through the early and late modern periods right up to the present day. It focuses in particular on transgressions of manners and norms of behaviour as an analytical tool to shed light on the discourse of polite conduct and styles of writing. The papers collected in this volume adopt both literary and linguistic perspectives. The fictional sources range from medieval romances and Shakespearean plays to eighteenth-century drama, Lewis Carroll's Alice books and present-day television comedy drama. The non-fictional data includes conduct books, medical debates and petitions written by lower class women in the eighteenth and nineteenth century. The contributions focus in particular on the following questions: What are the social and political ideologies behind rules of etiquette and norms of interaction, and what can we learn from blunders and other transgressions?"--